Insights into Native Fermentation Process of Apples (Malus domestica) in Low Sodium Conditions - Daniela Constandache (Lungeanu); Doina-Georgeta Andronoiu; Oana Viorela Nistor; Dana Iulia Moraru; Ira-Adeline Simionov; Elisabeta Botez; Gabriel-Dănuț Mocanu (Applied Sciences)
Although it is one of the most important methods of fruit and vegetable preservation, pickling provides multiple interesting vistas for study, from the variety of the raw vegetal material and the composition of pickling media to the diversity of the microorganisms involved in the process or the quality of the final product. The purpose of this study is to investigate the effects of sodium chloride substitution with potassium or magnesium chloride on the pickling process of apples. Physical (mass, color, texture), chemical (dry matter, acidity, salinity, reducing sugars) and phytochemical parameters of the apples were analyzed during 35 days of fermentation, with a frequency of 7 days. The results show a decrease in dry matter from 14.94 ± 0.25% for all the samples and a continuous increase of lactic acid concentration to a maximum of 0.248 ± 0.032 g lactic acid/100 g product for the magnesium samples. At the same time, the phytochemical profile is enhanced, while the texture becomes softer (a decrease in firmness from 2.53 ± 0.08 N to 0.72 ± 0.02 N was registered for potassium samples). The main conclusion of the study is that sodium chloride could be successfully replaced by potassium or magnesium chloride in the fermentation process of apples.